New insights into the molecular basis of induced resistance triggered by potassium phosphite in potato - Feldman, Mariana Laura; Guzzo, María Carla; Machinandiarena, Milagros Florencia; Rey Burusco, María Florencia; Beligni, María Verónica; Di Rienzo, Julio A.; Castellote, Martín Alfredo; Daleo, Gustavo Raúl; Andreu, Adriana Balbina (2020)
This work aimed to provide data about the molecules involved in induced resistance mediated by potassium phosphite (KPhi) in potato. To achieve these, we performed microarray analysis to determine the changes in gene expression after KPhi treatment, and their abundance after Phytophthora infestans (P.i.) infection. Our results showed the differential expression of 172 genes after KPhi treatment, and 22 KPhi primed genes after P.i. challenge, mainly involved in signal transduction and defense reactions, among others. Additionally, to identify common cis-elements involved in their regulation, we analyzed in-silico KPhi responsive genes promoters. Interestingly relevant phytohormone and stress-responsive cis-elements were present.